Some blood and milk constituents as affected by breed and pregnancy stage in rabbits - Marai I.F.M.; El Sayiad G.A.; Ayyat M.S. (Rabbit production in hot climates, 1994)
Blood and milk samples were collected from New Zealand White (NZW) and Californian (Cal) lactating does immediately before mating, at day 14 and day 28 of gestation period. The constituents estimated in blood (B) and milk (M) were prolactin, progesterone, total protein, total fat, sugar, calcium (Ca), magnesium (Mg), sodium (Na), potassium (K) as well as hemoglobin. Rectal temperature, respiratory and pulse rates were estimated. The results showed that Cal does generally exceed NZW ones significantly (P less than 0.01 and 0.05) in all traits studied either in blood or in milk, but M and B constituents of milk were manyfold those for blood, except Na which was about only two thirds of that of blood in milk. The mineral levels decreased gradually in the following order: Na, K, Ca to Mg in blood and Ca, K, Na to Mg in milk, respectively, in the two breeds studied. Each of prolactin and progesterone levels increased as milk yield increased, and decreased as pregnancy advanced (and milk yield decreased). Total protein (in B and M) and blood fat decreased, while milk fat, sugar and Na, generally increased as pregnancy and suckling advanced. The levels of minerals investigated (in B and M) were significantly (P less than 0.01) affected by pregnancy stage, except blood Mg which was not affected. Haemoglobin decreased and respiratory rate increased (P less than 0.01) with the advancement of pregnancy stage. Correlation coefficients between each pair of traits studied in blood and milk either within breed or pregnancy stage were mostly not significant and different in sign.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)